Articulating Fundamental Values through the European Quality Assurance Framework - Kelo, Maria (International Higher Education, 2025)
<h3 id="this-article-describes-the-current-debates-taking-place-in-the-revision-process-of-the-european-quality-assurance-framework-specifically-the-standards-and-guidelines-for-quality-assurance-in-the-european-higher-education-area-focusing-on-questions-related-to-the-evaluation-and-assessment-of-fundamental-academic-values-through-quality-assurance-standards" data-pm-slice="1 1 []">This article describes the current debates taking place in the revision process of the European quality assurance framework (specifically, the Standards and Guidelines for Quality Assurance in the European Higher Education Area), focusing on questions related to the evaluation and assessment of fundamental academic values through quality assurance standards.